Using the Anatomage Table to Facilitate Learning of Radiographic Anatomy, Positioning, and Image Evaluation. - Spence, Brian; Russell, Amy (Radiologic Science & Education, 2026)
The purpose of this study was to evaluate student learning and satisfaction with Anatomage Table review sessions in a radiographic procedures course. Twenty-nine first-year radiologic technology students participated in guided Anatomage Table review sessions during instructional units focused on the bony thorax and vertebral column. Student performance on the image identification, labeling, and evaluation components of laboratory examinations was compared to scores from the previous year's cohort, which did not include Anatomage Table activities. A paired samples t-test revealed a statistically significant difference in scores between cohorts (p = .039), with higher scores observed following implementation of the Anatomage Table sessions. In addition, 11 students completed a postcourse survey evaluating perceptions of the Anatomage Table as a learning tool. Most respondents (n = 9, 81.8%) reported increased knowledge of radiographic anatomy, positioning, and image evaluation, along with positive perceptions of engagement and usefulness. Although limited by a small sample size and single-institution design, the findings suggest that the Anatomage Table is a beneficial supplemental instructional tool for radiologic technology education. Future research with larger, multi-institutional samples is recommended to further evaluate its impact across radiologic technology curricula.